DERIVATION OF INDONESIAN LANGUAGE IN THREE INDONESIAN TEXTS - Abrar, Mukhlash (LearnING Journal, 2014)
This paper tries to analyze the derivational process in three Indonesian texts. The method of the research and data collection of this research is synchronic descriptive in which the data are collected and described naturally. The data of the research are taken from three Indonesian texts âSemarang Metroâ newspaper published on January 7th 2012. The writer uses substitution or agih method in analyzing the data. The result shows that there are 6 derivation affixes found in three Indonesian texts such as prefixes peN- and ber-, suffixes âan and âkan and also circumfix peN-an and ke-an. And the most derivation words found in three Indonesian texts are the derivational process by the addition of suffix âan. juï¿½ï¿½ o.F x7le, the researcher found nine types of mistakes namely misformation Â in using personal pronoun, misformation in using possessive pronoun, misformation in using demonstrative reference, misformation in using additional conjunction, misformation in using cause effect conjunction, omission of additional conjunction, omission opposite conjunction, omission of cause effect conjunction, misformation in using noun substitutionÂ